Sosialisasi Penerapan Softskill dan Hardskill Pada Sumber Daya Siswa Dalam Transaksi Keuangan Sosial Media di SMA Negeri 12 Surabaya - Dwi Dewianawati; Fajar Purwanto; Erry Setyawan; Buyung Perdana; Novrina Puspitasari; Ratna Agustina; Harjo Lukito (Journal of Community Development, 2025)
This community service activity aims to provide knowledge to SMA 12 Surabaya students about carrying out financial transactions on social media wisely and safely. According to Paais and Apituley (2023) the success of an individual is not only determined by his academic abilities (hard skills), but is also determined by soft skills, a skill needed so that an individual is able to manage his own emotions (intrapersonal skills) and is able to manage emotions when building relationships with others (interpersonal skills). The key to the formation of hard skills and soft skills is resources that are able and willing to change to become better. Student resources play an important role in financial transactions on social media. Some of the problems that exist include students' lack of knowledge about the dangers of making online transactions, and no knowledge about safe online transactions due to lack of information. Therefore, this activity aims to provide additional knowledge and insight about all buying and selling activities via social media, why transactions are made online, payment methods that can be used, and risks that can arise due to online transactions so that students can maximize their soft skills and hard skills. to maintain safe online transactions. Based on the results of the pre-test and post-test, there were 9 students in the "Poor" understanding category and only 1 student after that, in the "Enough" category before that there were 22 students and after that there were 6 students, in the "Good" category before that there were 8 students and after that showed an increase of 32 students. Thus, further community activities are needed regarding wider use of social media so that students can further develop their soft skills and hard skills.